Pengaruh Islamic Branding dan Religiusitas Terhadap Keputusan Pembelian Produk HNI-HPAI Halal Mart BC Medan 8 - Fitra Sulistina Wati (Yayasan Rahmat Islamiyah, 2021)
This research aims to analyze the influence of Islamic Branidng and Religiosity on the decision to purchase HNI-HPAI Halal Mart BC Medan 8 products. This research uses quantitative methods and associative research types. The population in this research were consumers of HNI-HPAI Halal Mart BC Medan 8 and the sample used was 68 people using purposive sampling. Data collection techniques used in this research are questionnaires, interviews and documentation. The analyctical method in this research used the validity and realibility of the data, the normality test, the classic assumption test, the multiple regression test, the hypothesis test and the linear coefficient of determination test. The results of the study show that: (1) Islamic Branding has a positive and significant effect on Purchase Decisions. The results of the calculations that have been carried out are the > was 0,020 < 0,05, which indicates is rejected and is accepted. (2) Religiosity has a positive and significant effect on purchasing decisions. The results of the calculations that have been carried out are t arithmetic values > sebesar 0,000 < 0,05, which indicates is rejected and . Simultaneously it is known that Islamic Branding and Religiosity have a significant effect on purchasing decisions for HNI-HPAI Halal Mart BC Medan 8 products with a significance number of > (26,583 > 3,14). Based on the coefficient determination test, it shows that the R-square value is 0.929 or 92.9%, it explains that the independent variables, namely Islamic Branding and Religiosity affect the Purchase Decision of HNI-HPAI Halal Mart BC Medan Products 8. While the remaining 7.1% is influenced by variables which were not investigated in this study.